Evaluasi Sistem Mine Dewatering Pada Seam C Tambang Batubara Bawah Tanah Pt. Allied Indo Coal Jaya Kota Sawahlunto - Loli Susanti; Murad Murad (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. In the underground mining system at the Seam C location of PT. Allied Indo Coal Jaya The problem that often occurs is that a lot of water enters or is inundated. Therefore a mine drainage system is needed to support mining activities, so that various infrastructures that are made aim to control the water that flows in the mining area, especially in the opening hole. The water handling system in this area is more concerned because it is directly related to mining activities that are always mobile, so the discharge of water that comes out must be in accordance with the flow of water that enters the mine.In the Seam C area it has 2 sumps and 7 control tanks, because the pumping system is carried out by flowing water from the work front to the control basin, and then to the last sump, then it is flowed out of the mine by relay. The types of pumps used are Airlux WQD6-12 0.55 (075 Kw) and Airlux WQ25-20-3 (3 Kw). The number of pumps currently in use is 9 units, due to the large amount of incoming groundwater discharge. Measurement of water discharge is done manually in the field by measuring water at the point which is the largest water source at the study site, front tunnel tunnel 3 and tunnel tunnel front 4. Based on the discussion and analysis of the data it can be concluded that groundwater discharge in tunnel 3 is 0.1485 (m3 / min) and tunnel 4 is 0.1454 (m3 / min) while runoff water discharge is 0.1692 (m3 / sec) and the amount 10 units of pump needed to dry water consist of 8 units of Airlux WQD6-12 0.55 (075 Kw) and 2 units of Airlux WQ25-20-3 (3 Kw).Keywords: Underground Mine, Mine Dewatering, Pumps, Groundwater Discharge, Runoff Discharge